Radiation induced heat shocked gynogenesis in mrigal Cirrhinus mrigala Hamilton - Mia, Md. Younus; Islam, Md. Shahidul; Shah, Md. Saifuddin (Indian Journal of Fisheries, 2011)
Gynogenesis was induced in mrigal Cirrhinus mrigala, by subjecting eggs fertilizedwith UV-irradiated sperm through heat shock. The sperm was inactivatedthrough UV-irradiation with 580 nw/cm^ at an exposure of 2 minutes at a constantdistance of 13.5 cm lamp-sperm. Gynogenetic diploidy was induced by restoringsecond polar body by sub-lethal heat shock at 39 to 40Â°C for 1 to 2 minutes,initiated 4 minutes after fertilization. Heat-shock regimes with the constantdose of UV-irradiation were optimized at 39Â°C for 2 minutes, applied 4minutes after fertilization. The triploids in the controls were induced at low ratesranging from 0 to 70% and haploids ranged from 50 to 100% with 0 to 8% survivalrates. Gynogenetics had poor survival rates which varied from 2 to 50% of whichsome individuals even could be triploids or normal diploids due to presumedinappropriate heat-shock and UV-irradiation. Survival rate of 30 to 60% wasrecorded in the control